Pelatihan Penerbitan Perangkat Pembelajaran Fisika melalui Google Play Books - Arifin, Fathul; Wijianti, Dewi Wahyu; Alsa, Fikri Nathiqrahman; Rose, Luthfiyah Dyaka; Sari, Yuni Mega; Hartini, Tri Isti (MJI Publisher by PT Mitra Jurnal Indonesia, 2023)
Abstract Based on the needs analysis observations using the 3E framework (Empathy, Expansive Thinking, and Execute), the results show that most of the JT II MGMP physics teachers still need physics material review and support media in the form of teaching materialsintegrated with the Google Play Books application to design differentiated learning in Phase F Class XI of the Merdeka Curriculum. The method used in this activity is online discussion and training. The responses of the participants were measured through a survey at the end of the training. Based on the survey results, 56.4% of the participants stated that this training had represented the needs of physics learning, 57.8% of the participants stated that the training results could be applied in learning, and 60.9% of the participants stated that the presentation of the material was complete and clear, the three results were included in the satisfactory category. Based on these results, it can be concluded that the training went well. Abstrak Berdasarkan observasi analisis kebutuhan dengan menggunakan kerangka berpikir 3E (Empathy, Expansive Thinking, dan Execute) diperoleh hasil bahwa sebagian besar guru Fisika MGMP JT II masih memerlukan bedah materi Fisika, dan media pendukung berupa bahan ajar yang terintegrasi pada aplikasi Google Play Books untuk merancang pembelajaran berdiferensiasi pada Fase F kelas XI Kurikulum Merdeka. Metode yang digunakan dalam kegiatan ini adalah diskusi dan pelatihan secara daring. Respon peserta diukur dengan menggunakan kuesioner di akhir pelatihan. Berdasarkan hasil survei, 56,4% peserta menyatakan pelatihan ini sudah mewakili kebutuhan pembelajaran fisika, 57,8% peserta menyatakan hasil pelatihan dapat diterapkan dalam pembelajaran, dan 60,9% peserta menyatakan pemaparan materi sudah lengkap dan jelas, ketiga hasil tersebut termasuk dalam kategori memuaskan. Berdasarkan hasil tersebut dapat disimpulkan bahwa pelatihan yang dilakukan sudah berjalan dengan baik.